Sharia Cooperatives as a Means of Community Economic Empowerment: A Case Study on Microenterprise Cooperatives in West Java - Rokibulloh (Sekolah Tinggi Agama Islam Kuningan, 2025)
This research discusses the role of Islamic cooperatives in community economic empowerment, especially for micro-enterprise cooperatives in West Java. The global economy, which is facing challenges of inequality and poverty, encourages the importance of community-based empowerment, one of which is through Islamic cooperatives that provide solutions to access financing based on sharia principles. The purpose of this study is to analyze the role of Islamic cooperatives in community economic empowerment, explore the challenges and opportunities of Islamic cooperative management, and its impact on the welfare of cooperative members. This research uses a qualitative approach with descriptive methods. Data were obtained through in-depth interviews, observation, and documentation of Islamic cooperatives in West Java. The results show that Islamic cooperatives can increase access to financing for micro businesses, but are faced with the challenges of suboptimal financial management and a lack of understanding of sharia principles among members. The implications of this research suggest managerial improvement and technology utilization in the management of Islamic cooperatives to improve transparency, efficiency, and sustainability of cooperatives in the future.